The Newton-like properties of the updating mechanism of a model-reality differences algorithm - Ahmad, Rohanin; Abd. Aziz, Mohd. Ismail (Department of Mathematics, Faculty of Science, 2003)
The Dynamic Integrated Systems Optimization and Parameter Estimation (DISOPE) algorithm is an algorithm for solving nonlinear optimal control problems and is of the gradient descent type. The updating step of DISOPE plays an important role in terminating the iterations of the algorithm and hence in determining its rate of convergence. In this paper, the mechanism was shown to have Newton-like properties and the order convergence established